What do managers think about the success potential of CRM campaigns? - Castanheira, Bruna Monteiro (2020)
This research analyzes cause-related marketing (CrM) from the perspective of companies. The study aims to achieve a better understanding about what managers think about CrM by analyzing the level of acceptance and usage of this marketing tool, based on the UTAUT model. Using in-depth interviews as research method, we conclude that managers see the benefit of company partaken in initiatives as such, but not necessarily CrM. The reasons why managers choose to participate in Cause-related Marketing initiatives originate from the mix obtained through improving the firm by doing something considered socially positive. CrM was well evaluated by the participants and considered well positioned in terms of acceptance and usage, based on four factors: performance and effort expectancy, social influence, and facilitating conditions. Interviewees expressed excitement towards CrM and believe in it as a powerful tool to improve the firms’ image and consumers feeling towards it. While the literature uses several concepts (Corporate Social Responsibility or Social Marketing), the interviewees emphasize genuine caring and showing interest, time and funds to support consumers social concerns.